Modelling and Passivity-based Control of a Non-isolated DC-DC Converter in a Fuel Cell System - Moutabir Ahmed; Abdelmounim Elhassane; Aboulfatah Mohamed (Institute of Advanced Engineering and Science, 2018)
This paper presents the model of a fuel cell and the design and simulation of a cascade of two DC-DC converters. First, a detailed mathematical model of fuel cell is presented and simulated. Then, a nonlinear model of the whole controlled system is developed and a robust nonlinear controller of currents is synthesized using a passivity-based control. A formal analysis based on Lyapunov stability and average theory is developed to describe the control currents loops performances. A classical PI controller is used for the voltages loops. The simulation models have been developed and tested in the MATLAB/SIMULINK. Simulated results are displayed to validate the feasibility and the effectiveness of the proposed strategy.